Can we have synthetic philosophy - Krzanowski, Roman (Człowiek i Społeczeństwo, 2025)
This paper concerns synthetic philosophy, or philosophy created by a computer system. We discuss when a work created by a computer system can be called a work of philosophy and when it cannot. We question the kind of philosophy that synthetic philosophy could be, as well as what kind of philosophical vistas it could open to us. Furthermore, we also delve into who would be responsible for the ethical impact from computer-generated philosophical works. Finally, we speculate about the possible future of synthetic philosophy with ai technologies that have yet to be created.